Association between T‐tau protein and Aβ42 in plasma neuronal‐derived exosomes and cognitive impairment in patients with permanent atrial fibrillation and the role of anticoagulant therapy and inflammatory mechanisms. Issue 4 (1st February 2022) - Du, Meiling; Wang, Xiaoyuan; Ma, Fei; Li, Fangjiang; Li, Huixian; Li, Feixing; Zhang, Aiai; Gao, Yuxia
Abstract: Background: This study explores whether the differences in cognitive performance among individuals with permanent atrial fibrillation (AF) are attributable to the duration of AF and anticoagulant therapy and explores the possible inflammatory mechanism of cognitive dysfunction related to AF. Methods: A total of 260 patients aged 50–75 years without previous cerebrovascular events were enrolled in this study. These 260 patients had been divided into the AF group (140 patients) and sinus rhythm group (120 patients). In the AF group, we divided participants into cognitive impairment (CI) group (90 patients) and cognitive normal (CN) group (50 patients). In the sinus rhythm group, we also divided participants into CI group (61 patients) and CN group (59 patients). The Mini‐Mental State Examination (MMSE) was used to assess the cognitive function of all participants. Neuronal‐derived exosomes were enriched in peripheral blood by immunoprecipitation and were confirmed by a transmission electron microscope, nanoparticle tracking analysis, and western blot. Alzheimer's disease‐pathogenic exosomal proteins and inflammatory cytokines were quantified. The association between AF and cognitive function was estimated by logistic regression analysis. ANOVA or Welch's t ‐test compared the difference in protein concentrations between groups. Results: Non‐anticoagulant therapy in patients with AF was significantly associated with CI (OR = 13.99, 95% CI: 2.67–73.36, p < .01). The incidence of dementia in patients with AF > 3 years was significantly higher than in patients with AF ≤ 3 years, but there was no significant difference in total cognitive dysfunction (mild cognitive impairment [MCI] + dementia) ( p = .126). The adjusted exosome concentrations of T‐tau and amyloidβ protein 42 (Aβ42) in the CI group were significantly higher than in the CN group ( p < .001). The serum concentrations of IL‐6 and matrix metalloproteinase‐9 (MMP‐9) in patients with AF were higher than those in patients with sinus rhythm ( p < .001). Conclusion: Aβ42 and T‐tau in peripheral blood neuronal‐derived exosomes maybe be associated with the early diagnosis of CI in patients with permanent AF. However, the value of Aβ42 and T‐tau for CI in patients with permanent AF still needs to be confirmed in future randomized control trials.